Shoot for the Stars? Predicting the Recruitment of Prestigious Directors at Newly Public Firms - Acharya, Abhijith G.; Pollock, Timothy G. (Academy of Management Journal, 2013)
This study explores how CEOs' and outside directors' desires for the benefits of signaling and “homophily” intertwine with their concerns over maintaining power and preserving local status hierarchies to affect the likelihood a firm recruits prestigious outside directors to its board. Using pooled cross-sectional data on the five years following the initial public offerings (IPOs) of 210 firms that went public between 2001 and 2004, we found that prestigious CEOs and directors viewed the recruitment of prestigious new directors differently and that these perceptions were moderated by factors that increase the salience of risk of potential losses to CEOs and existing board members.